2012
DOI: 10.1038/ncb2521
|View full text |Cite
|
Sign up to set email alerts
|

The H19 lincRNA is a developmental reservoir of miR-675 that suppresses growth and Igf1r

Abstract: The H19 large intergenic noncoding RNA (lincRNA) is one of the most highly abundant and conserved transcripts in mammalian development, being expressed in both embryonic and extraembryonic cell lineages, yet its physiological function is unknown. Here we show that miR-675, a microRNA (miRNA) embedded within H19’s first exon, is expressed exclusively in the placenta from the gestational time point when placental growth normally ceases, and placentas that lack H19 continue to grow. Overexpression of miR-675 in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
617
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 733 publications
(645 citation statements)
references
References 48 publications
15
617
0
4
Order By: Relevance
“…We observed that H19 +/hIC1 placentas not only are smaller, but also have abnormal placental morphology. Although the contribution of an abnormal placenta to fetal growth defects is unclear, it is noteworthy that H19 is more highly expressed in the labyrinthine zone compared with the junctional zone (38), and that Igf2 null mice display a disproportionate reduction in the labyrinthine zone compared with the junctional zone (39). These observations suggest a potential major growth-suppressing effect of increased H19 and silenced Igf2 expression in the labyrinthine zone.…”
Section: Resultsmentioning
confidence: 60%
“…We observed that H19 +/hIC1 placentas not only are smaller, but also have abnormal placental morphology. Although the contribution of an abnormal placenta to fetal growth defects is unclear, it is noteworthy that H19 is more highly expressed in the labyrinthine zone compared with the junctional zone (38), and that Igf2 null mice display a disproportionate reduction in the labyrinthine zone compared with the junctional zone (39). These observations suggest a potential major growth-suppressing effect of increased H19 and silenced Igf2 expression in the labyrinthine zone.…”
Section: Resultsmentioning
confidence: 60%
“…It has been reported that GAS5 RNA serves as a false target of transcription factor GR to prevent the binding of GR to the promoter DNA [28]; an lncRNA derived from the secondary promoter of DHFR can bind in cis the primary promoter to form a DNA-RNA triplet, resulting in blocked recruitment of TFIID, a transcriptional regulation cofactor, to the primary promoter and the subsequent transcription repression [29]; linc-MD1 RNA acts as miRNA sponge to suppress the activities of miR-133 and miR-135, resulting in increased levels of miRNA targets and the ultimate influence on muscle differentiation [30]. In conclusion, the accumulated studies show that lncRNAs not only serve as the precursors of certain small ncRNAs, such as miR-675 encoded by the H19 lncRNA [24,31], but also present a class of regulatory RNAs fundamentally distinct from the small ncRNAs, which appear to play roles through the mechanism of interaction with DNA, RNA or protein.…”
Section: Biological Features Of Lncrnasmentioning
confidence: 99%
“…The ncRNAs as described to be produced by some viruses are hundreds to thousands of nucleotides in length and may have the ability to regulate gene expression in favor of the viral genome [121]. There are examples of long and short ncRNAs intersecting with each other and lncRNAs can themselves be host genes for small RNAs, for example H19 is host to microRNA-675 [122].…”
Section: Long Non-coding Rnasmentioning
confidence: 99%